Perancangan Aplikasi Android pada Alat Monitoring Kecelakaan dengan Intellegent Transport System - Muhammad Dandy Pratama Putra; Ade Silvia Handayani; Ing. Ahmad Taqwa; Nyayu Latifah Husni; Leni Novianti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The increasing number of transportation also increases the number of traffic accidents. It can happen not only in the open road but also in the quiet road so that the bad things can happen to the accident victims. The delays of handling the accidents often occur due to the delay information that received by the police or the nearest hospital. This is due to the information that obtained by local people and forwarded to the authorities is slow. Therefore a system that can monitor the vehicle remotely will be needed nowdays. By building an accident monitoring system using the Intelligent Transport System (ITS), it is hoped that it can monitor the vehicle and through Android can directly check the coordinates of the vehicle and the condition of the vehicle. In the design of the accident monitoring system tool using the SVM (Support Vector Machine) method. Testing this tool uses hardware consisting of Rasberry PI 3, Arduino Uno, Sensor FC04, Accelerometer 6050, Vibration Shock Sensor, Camera Pi Noir, panic button, GPS and Android Application as an interface with the user. The results of this research show that the tool made has a percentage of delays between 1 to 5 seconds, all data from the accident monitoring system tool is directly sent to the Android application in real time based on the internet network speed connection